Physics programme of ALICE 3: A next-generation heavy-ion detector for LHC Run 5 and beyond - Nicassio Nicola (EPJ Web of Conferences)
The ALICE Collaboration is designing a completely new apparatus, ALICE 3, for the LHC Runs 5 and 6. The detector comprises a large pixel-based tracking system covering eight units of pseudorapidity, complemented by various particle identification systems including silicon time-of-flight layers, a ring-imaging Cherenkov detector, a muon identification system, an electromagnetic calorimeter and a forward conversion tracker. ALICE 3 will, on the one hand, enable novel studies of the quark-gluon plasma (QGP) and, on the other hand, open up important physics opportunities in other areas of QCD and beyond. The main new studies in the QGP sector focus on low-pT heavy-flavour production, including beauty hadrons, multi-charm baryons and charm-charm correlations, as well as on precise multi-differential measurements of dielectrons to probe the mechanism of chiral-symmetry restoration and the time-evolution of the QGP temperature. Besides QGP studies, ALICE 3 can uniquely contribute to hadronic physics, with femtoscopic studies of the interaction potentials between charm mesons and searches for nuclei with charm, and to fundamental physics, with tests of the Low theorem for ultra-soft photon emission. This contribution will cover the latest detector concept and the state-of-the-art projections for the resulting physics performance in dielectron and heavy-flavour measurements.